The role of motion verbs in conveying path-related information in English and Slovene fictive motion expressions - Lipovšek, Frančiška (ELOPE (Ljubljana), 2018)
The paper presents a study on fictive motion (FM) uses of motion verbs in English and Slovene from the point of view of conveying path-related information. An FM expression describes a static scene in terms of motion (e.g. The road weaves through a range of hills). Motion verbs in FM uses do not describe actual motion events, but may refer to certain properties of the path by virtue of their meanings. English and Slovene FM expressions exhibit different behaviours in this respect. Many English verbs display meaning components that can be metonymically mapped onto the properties of the path. The meanings of Slovene verbs are less specific, so that such properties need to be expressed verb-externally in Slovene FM expressions.
Keywords: fiktivno gibanje; glagoli premikanja; metonimična preslikava; metonimija; način premikanja; pot